Microsurgical outcome of unruptured giant intracranial aneurysms: A single-center experience. (December 2019) - Li, Maogui; Ma, Yonggang; Jiang, Pengjun; Wu, Jun; Cao, Yong; Wang, Shuo
Highlights: Whether direct clipping is the first choice for giant aneurysms is pending. No worse prognosis was obtained in unclippable GIAs compared with clippable ones. Favorable outcomes can be obtained in most GIA patients after appropriate microsurgical procedure. Abstract: Microsurgical treatment of unruptured giant intracranial aneurysms (GIAs) is challenging. Although previous studies regarded clipping as the first option to repair GIAs, quite a number of GIAs are not clippable. We conducted this study to evaluate the postoperative complications and long-term outcome of patients with unruptured GIAs treated by different microsurgical modalities. We retrospectively reviewed 505 consecutive patients with unruptured intracranial aneurysms (UIAs) who were surgically treated in our department from 2012 to 2015. Patients with UIAs of which diameter ≥2.5 cm were studied. We reported the characteristics of patients and GIAs. Postoperative major complications were observed, and patient functional status were assessed with the modified Rankin Scale (mRS) at discharge and at the last follow-up. Twenty-one patients with unruptured GIAs were analysed, of whom 12 patients were treated by clipping, whereas 9 patients with unclippable aneurysms were treated by trapping or parent vessel occlusion. Fourteen aneurysms were saccular, and 7 were fusiform or serpentine. The mean aneurysm size was 3.7 ± 1.5 cm. After surgery, major complications were observed in 13 of the 21 (61.9%) patients. One (4.8%) patient died during hospital. After a mean 5.2-year follow-up, 9 (75.0%) patients treated by clipping and 7 (77.8%) treated by non-clipping experienced a good outcome (mRS ≤2). We found no significant difference in both postoperative complications and long-term outcome between clipping and non-clipping group. Favorable prognosis can be obtained in most patients with unruptured GIAs treated by appropriate microsurgical modality.